Beverages application with personalized health management - Kong, Phui Yin (2024)
This project endeavors to develop a beverage application integrated with a personalized health management system to address deficiencies in existing beverage applications. The objectives focused on implementing drink recommendations, enhancing health management features, and improving categorization. Leveraging industry trends and successful models like Zus Coffee, the project utilized React Native for cross-platform compatibility, APIs for weather-based recommendations, and Firebase for data management. The review of existing applications highlighted gaps in recommendation systems, health management tools, and categorization features, underscoring the need for innovation. The implementation phase prioritized user-centric design, incorporating personalized drink recommendations, health alerts, and efficient categorization and search functionalities. Black box testing evaluated user and admin functionalities, validating successful implementation of objectives. The evaluation of the project's success is based on several key criteria. The implementation of drink recommendation features was validated through user testing, assessing the effectiveness of weather-based recommendations and user preferences. Health management tools were evaluated based on user engagement with health alerts and guidance. The categorization and search functionalities were tested for usability and efficiency, ensuring ease of navigation and access to beverage options. Black box testing provided insights into the application's performance across user and admin interfaces, highlighting strengths and areas for improvement. User feedback and satisfaction surveys were instrumental in assessing the application's impact on user experience and wellness promotion. Overall, the project's success is measured by its ability to address user needs, enhance engagement, and promote healthier beverage choices through innovative digital solutions.